Reducing morbidity in second stage cesarean section by Patwardhan’s (shoulders first) method of delivery - Kumari, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: To evaluate Patwardhan’s method of delivering shoulders first during second stage cesarean section. Methods: 154 consecutive cases of cesarean section for second stage arrest or obstructed labor over a period of one year (July 2016 to June 2017) were included in the study. 77 cases delivered by Patwardhan’s method comprised of study group and 70 cases delivered by vertex, 7 cases delivered by breech served as control. Fetal and maternal outcomes were compared in these two groups. Results: Obstetric features like parity, maternal height, duration of pregnancy, hemoglobin levels, fetal weight were comparable in both groups. Perinatal outcomes were almost similar in both the groups. Extension of the uterine incision occurred in only 4 cases (5.19%) in the study group compared to 16 cases (20.77%) in control group. Excessive bleeding, uterine artery injury, need for blood transfusion and hysterectomy were also less in the study group. Conclusions: Morbidity due to extension of uterine incision occurs commonly during second stage cesarean section, when hand is forcibly introduced in the pelvis to deliver impacted head, since lower uterine segment is edematous and fragile. Patwardhan’s technique avoids this and hence should be practiced more widely. Its beauty lies in near absence of extension of uterine incision.